Tanggap Bencana Mahasiswa KKN STIBA Makassar Melalui Pembinaan Rohani Masyarakat Desa Kabiraan Kabupaten Majene - Aswar Aswar; Iskandar Iskandar; Syandri Syandri (WAHATUL MUJTAMA': Jurnal Pengabdian Masyarakat, 2021)
The purpose of STIBA Makassar Real Work Lecture (KKN) with the concept of “KKN Kemanusiaan of West Sulawesi” is to realize community service which is a pillar of “Tri Darma Perguruan Tinggi”. The method of implementing this program is to map the problem using SOAR analysis. After analyzing the problems and needs of the community, several appropriate work programs are prepared. Successful work programs are Dirosah Method of Al-Qur’an Learning, Weekly Taklim, Community Service, Tablig Akbar, TK/ TPA, Clean Friday, and others. The results of the activities showed that STIBA students are able to serve the people affected by the disaster seriously so that they get a lot of social experience. The community of Ulumanda, especially in Kabiraan village, feel very helped by the presence of students during KKN there and fully support the implementation of “KKN Kemanusiaan STIBA Makassar” for the recovery of the state of the community after the earthquake disaster. All parties expect the sustainability of KKN activities in terms of construction both formally and non-formally for Kabiraan village.